The Adoption of International Financial Report Standards and Corruption - Li, Huan. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2022.; Submitted to the Dept. of Economics.; Advisors: Yannis Ioannides, and Enrico Spolaore.; Committee: Melissa McInerney.; Keyword: Economics.